The effect of moisture, litter and stand age on N fixation in the feathermoss, Pleurozium schreberi - Gustafsson, Helena (2008)
The largest known natural input of nitrogen (N) into the boreal forests occurs through biological fixation by cyanobacteria that live in association with the moss Pleurozium schreberi. There is currently limited knowledge about the factors responsible for the variation in N fixation rates, and specifically what factors drive variability between stands. In this study I have studied the N fixation rate on P. schreberi in a watering experiment and a litter extract experiment. In the water experiment the effect of frequency of water additions were studied, while in the litter experiment the effects of litter extracts of the three most common tree species and three of the most common dwarf shrub species of the boreal forest were studied. The moss was collected from three young successional sites and three old successional sites after fire. The study was performed in a greenhouse for a period of 45 days and N fixation rates were estimated after 13, 21 and 45, 43 days for water experiment and litter experiment respectively using a calibrated acetylene reduction technique. I found that the mosses collected from young stands had significantly lower N fixation rates compared to mosses collected from old stands. Watering treatments had a significantly positive effect on N fixation rates in mosses originating from old, but not from young stands. The watering effect on the N fixation rate was increasing from measurement on the 13th day of treatment to day 45. For the litter extract experiment, no significant effect of any litter type was detected. These results suggest that micro variation at the stand level in water availability is likely a more important determinant of ecosystem N fixation rates in old successional forests than is the deposition of foliar compounds on moss carpets.